Influence of Asthma on the Longitudinal Trajectories of Cigarette Use Behaviors From Adolescence to Adulthood Using Latent Growth Curve Models - Jisuk Bae (Korean Society for Preventive Medicine, 2015)
Objectives: While epidemiologic research indicates that the prevalence of risk-taking behaviors including cigarette smoking among young people with asthma is substantial, the longitudinal patterns of cigarette smoking in this vulnerable population have received little attention. The aim of this study was to evaluate differences in the longitudinal trajectories of cigarette use behaviors from adolescence to adulthood between young people with and without asthma. Methods: Data from the National Longitudinal Study of Adolescent to Adult Health (Add Health) during the years 1994 to 1995 (Wave I, adolescence), 2001 to 2002 (Wave III, young adulthood), and 2007 to 2008 (Wave IV, adulthood) were analyzed (n=12 244). Latent growth curve models were used to examine the longitudinal trajectories of cigarette use behaviors during the transition to adulthood according to asthma status. Results: Regardless of asthma status, the trajectory means of cigarette use behaviors were found to increase, and then slightly decrease from adolescence to adulthood. In total participants, there were no statistically significant differences in initial levels and changes in cigarette use behaviors according to asthma status. However, in select sex and race subgroups (i.e., females and non-whites), former asthmatics showed greater escalation in cigarette use behaviors than did non-asthmatics or current asthmatics. Conclusions: This study indicated that the changing patterns of cigarette use behaviors during the transition to adulthood among young people with asthma are comparable to or even more drastic than those among young people without asthma.